FRI0016 IGE as a Biomarker of Regulatory T Cell Activity in Autoimmune Diseases. (9th June 2015) - Moraes-Fontes, M.F.; Costa, N.; Santos, C.; Coutinho, A.; Fesel, C.
Abstract : Background: Regulatory T cell (Treg) defects are associated with autoimmune diseases [1]. Immunoglobulin E (IgE) is elevated in primary immunodeficiencies associated to Regulatory T cell (Treg) defects [2] and is known to be positively correlated to disease activity in Systemic Lupus Erythematosus (SLE) [3, 4]. More specifically, Treg frequency (increased) and CD25 expression (decreased) are dissociated in patients with active SLE [5, 6]. Objectives: To establish the relationship between circulating Treg frequency/number and phenotype and total IgE/IgE auto-antibodies and test the hypothesis that total IgE could be a marker of a generalized Treg deficit. Methods: We first tested a large cross-sectional collection of plasma samples from unselected patients with a diagnosis of SLE according to ACR criteria (n=123) and from healthy controls (n=153). We then started a prospective longitudinal study of SLE patients (n=33, 30 females, mean age 41±10 years). A median of 4 samples were obtained per patient. Clinical characteristics, SLEDAI 2 K as index of disease activity, SELENA-SLEDAI score for definition of flare and sample collection were undertaken. During follow-up 13/33 patients experienced a flare. Samples were analysed by an ELISA "in house" method optimized for total IgE, antigen-specific IgE (anti-DNA, Sm, RNP), IgG anti-DNA and IgG anti-Sm. FACS analysis determined Treg frequency (CD4 + CD45RO + Foxp3 high ) and CD25 MFI expression. The Mann-Whiney Test and Spearman correlation were used with values of p<0.05 considered significant. Results: While there was no significant difference in total IgE, IgE anti-DNA was higher in patients (p=0.02) and positively correlated with SLEDAI (p=0.009). In the longitudinal prospective collection there was a positive correlation between IgG anti-DNA (p=0.002) or IgE anti-DNA (p=0.0003) and disease activity. IgE anti-DNA was increased in some patients with high SLEDAI and no IgG anti-DNA. The frequency of active Treg was positively correlated with SLEDAI (p=0.006) and with IgG anti-DNA (p=0.0004) while their CD25 expression was negatively correlated with SLEDAI (p=0.008) and IgG anti-DNA (p=0.002). There was no association between total IgE or IgE anti-DNA and Treg frequency or CD25 expression in either the cross-sectional study or the longitudinal patient collection. Conclusions: These results indicate that unlike IgG anti-DNA, IgE anti-DNA is not associated with Treg frequency or CD25 expression, raising questions regarding its affinity and pathogenicity. Still, as previously described, IgE anti-DNA behaved as a biomarker of SLE disease activity. In this study we demonstrate that it may be a useful biomarker in the absence of IgG anti-DNA. References: Bennett Nat Genet 2001 27(1):20-1. Ozcan J Allergy Clin Immunol 2008. 122(6):1054-62. Charles Nat Med 2010 16(6):701-7. Dema Plos One 2014 9(2)e90424. Bonelli Ann Rheum Dis 2008 67(5):664-71. Suen Immunology 2009 127(2):196-205. Acknowledgements: Jocelyne Demengeot (JD) for grant submission and ongoing support, JD, W Haas and J Lafaille for helpful discussions and R van Vollenhoven for scientific input. Staff at UIC and ICBAS (Porto), HSM, CHLO, Santarém, HFF, HCC and Patients and Patient Association for sample collections. Funding FCT EXPL/DTP-PIC/0644/2012 Disclosure of Interest: None declared